Child and parent outcomes following parent interventions for child emotional and behavioral problems in autism spectrum disorders: A systematic review and meta-analysis. (October 2019) - Tarver, Joanne; Palmer, Melanie; Webb, Sophie; Scott, Stephen; Slonims, Vicky; Simonoff, Emily; Charman, Tony
There is growing interest in the development of behavioral parent interventions targeting emotional and behavioral problems in children with autism spectrum disorders. Such interventions have potential to improve a number of child and parental well-being outcomes beyond disruptive child behavior. This systematic review and meta-analysis assesses evidence for the efficacy of behavioral parent interventions for disruptive and hyperactive child behavior in autism spectrum disorders, as well as parenting efficacy and stress. A total of 11 articles from nine randomized controlled trials were included. Sufficient data were available to calculate standardized mean difference and show favorable effects of behavioral parent interventions on parent-reported measures of child disruptive behavior (standardized mean difference = 0.67), hyperactivity (standardized mean difference = 0.31) and parent stress (standardized mean difference = 0.37); effects on parent efficacy are less clear (standardized mean difference = 0.39, p = 0.17). There were insufficient data to explore intervention effects on internalizing behavior in autism spectrum disorders, parenting behaviors, or observational and teacher-reported outcomes, providing important avenues for future research. This review adds to growing evidence of the efficacy of behavioral parent interventions for child behavior and parental well-being in autism spectrum disorders (Prospero: CRD42016033979).